Meteoric 10Be, grain size, surface area data for Rio Bermejo suspended sediment depth profile samples - Marisa N Repasch; Hella Wittmann; Joel S Scheingross; Dirk Sachse; Ricardo N Szupiany; Oscar Orfeo; Margret C Fuchs; Niels Hovius (PANGAEA, 2020)
To test the potential of meteoric 10Be (10Bem) as a river sediment transit time proxy, we measured 10Bem concentrations in river suspended sediment of the Rio Bermejo (northern Argentina), which is a river with a ~1300 km lowland flowpath void of tributaries. We collected fluvial suspended sediment in vertical depth profiles at five sampling locations along the length of the Rio Bermejo (northern Argentina) during near-bankfull conditions, when discharge varied between 675 and 1080 m**3/s and banks were actively eroding. Additionally, we collected one depth profile from Rio San Francisco (RSF) and one from the Rio Bermejo 10 km upstream of the RSF confluence. Combining these profiles and weighting them by the relative proportions of their total sediment load input to the mainstem Bermejo serves as an integrated headwater depth profile. In the thalweg, we collected water and suspended sediment from a boat using a weighted 8-liter horizontal sampling bottle (Wildco Beta Plus bottle) with an attached pressure transducer to measure sampling depth. We separated sediment from the water using a custom-built 5-liter pressurized filtration unit with a 293 mm diameter, 0.2 μm polyethersulfone filter. In the laboratory, we rinsed sediment off the filters directly into an evaporating dish with ultrapure 18.2 MΩ water (pH~7; when needed, we added NH3 solution to the water to maintain pH~7). Samples were dried in an oven at 40C, and subsequently homogenized. Sediment particle size distributions were measured on ~10 mg aliquots using a laser diffraction particle size analyzer (Horiba LA-950). Specific surface area (SSA) of bulk sediment samples was measured on ~4 g aliquots using a Quantachrome NOVAtouch LX gas sorption analyzer and the Brunauer, Emmett, and Teller (BET) theory (Brunauer et al., 1938). The total reactive phase, including amorphous oxyhydroxides and crystalline oxide grain coatings, was extracted from the sediment samples using a procedure adapted from Wittmann et al. (2012, doi:10.1016/j.chemgeo.2012.04.031). 10Bem was purified from the extracted material, spiked with a 9Be carrier solution containing 150 μg of 9Be, and packed into targets for AMS measurement at the University of Cologne Centre for Accelerator Mass Spectrometry (Cologne, Germany). 10Be /9Be measurements were normalized to the KN01-6-2 and KN01-5-3 standards (Dewald et al., 2013, doi:10.1016/j.nimb.2012.04.030) that are consistent with a 10Be half-life of 1.36 ± 0.07 x10^6 yr?^1 (Nishiizumi et al., 2007, doi:10.1016/j.nimb.2007.01.297). [10Be]m was calculated from the normalized and blank-corrected 10Be/9Be ratios. The reported 1σ uncertainties include counting statistics and the uncertainties of both standard normalization and blank correction. Stable 9Be concentrations were measured on a separate aliquot of the sample solution using inductively coupled plasma optical emission spectroscopy (ICP-OES). Uncertainty of ICP-OES measurements was 5%.